A STRATEGI IMPLEMENTASI KURIKULUM MERDEKA PADA SEKOLAH PENGGERAK : TINJAUAN LITERATUR SISTEMATIS: TINJAUAN LITERATUR SISTEMATIS - Mei Dwi Purwanti; Hendratno; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The independent curriculum is a curriculum with diverse intracurricular learning where content will be optimized so that learners have enough time to explore concepts and strengthen competencies. This study aims to ascertain and collect data related to the implementation of the independent curriculum in driving schools. This study is a systematic literature review, which aims to comprehensively review research related to the implementation of the independent curriculum in driving schools. The articles used were from 2022-2023. Principals and driving teachers have a major role in the implementation of the independent curriculum in driving schools. In its implementation, of course, obstacles are found. In addition, this study also describes activities in learning the independent curriculum. Keywords: Keywords: implementation, Merdeka curriculum, driving school